Generalized Eilenberg Theorem I: Local Varieties of Languages - Adámek, Jiří; Milius, Stefan; Myers, Robert; Urbat, Henning; Urbat, Henning (Foundations of Software Science and Computation Structures, 2014)
We investigate the duality between algebraic and coalgebraic recognition of languages to derive a generalization of the local version of Eilenberg's theorem. This theorem states that the lattice of all boolean algebras of regular languages over an alphabet Σ closed under derivatives is isomorphic to the lattice of all pseudovarieties of Σ-generated monoids. By applying our method to different categories, we obtain three related results: one, due to Gehrke, Grigorieff and Pin, weakens boolean algebras to distributive lattices, one due to Polák weakens them to join-semilattices, and the last one considers vector spaces over ℤ2. © 2014 Springer-Verlag.
UnivIS-Import:2015-04-17:Pub.2014.tech.IMMD.profes_1.genera